The logical evolution of internet governance policy in China from 1994-2017: A computational textual analysis approach - Jun Wu (International Telecommunications Society (ITS), 2018)
As China government gives full play to the role of digital technology in driving and leading the development of economy and society, policy issues on China internet governance have gained wide attractions from academics and practitioners. Grounded on a unique textual dataset collected from China official law and regulation database with over 300 central and local government laws and regulations on internet governance released during the period of 1994 and 2017,this study investigates the evolutional characteristics of the policy central topics, policy subjective and policy orientation in the timeframe of 1994 to 2017.This paper contributes to the existing knowledge accumulation not only in its uncovering of the evolutional logic hidden in the large swaths of policy text but also by introducing a computational text analysis approach to facilitate the text oriented policy evaluation.
Keywords: 330; Internet governance；regulation policy；China; Topic modeling